Effect of etching temperature on surface properties of Ti6Al4V alloy for use in biomedical applications - Alberti, Charles Jourdan [UNESP] (2019)
The objective of this study is to evaluate the surface physicochemical properties of Ti6Al4V alloy after etching with a piranha's solution at temperatures of 25 °C, 40 °C, and 60 °C for 30 min. Scanning electron microscopy with energy-dispersive X-ray spectroscopy, optical profilometry, X-ray diffraction, and wettability analyses were used to characterize the surface of the samples. In addition, corrosion tests were performed using potentiodynamic polarization and electrochemical impedance spectroscopy. The proposed surface treatment did not alter the wettability and surface chemistry (crystallinity), but the texture, surface roughness, superficial area, and corrosion resistance of the alloy could be changed by varying the etching temperature. Considering that these properties are indirect indicators of the alloy's potential success in the osseointegration of a dental implant, the surface treatment of the Ti6Al4V alloy using a piranha solution while controlling the etching temperature has attractive biomedical applications.